Vertical-algal-biofilm enhanced raceway pond for cost-effective wastewater treatment and value-added products production. (1st August 2018) - Zhang, Qi; Yu, Zhigang; Zhu, Liandong; Ye, Ting; Zuo, Jiaolan; Li, Xuemei; Xiao, Bo; Jin, Shiping
Abstract: A win-win strategy by the integration of wastewater treatment with value-added products production through a vertical-algal-biofilm enhanced raceway was investigated in the present study. Raceway pond was enhanced by vertically setting the biofilm in the system with a certain interval distance that could be adjusted for different light conditions and wastewater types. Two types of synthetic wastewater were treated with suitability-proven materials as biofilm carriers under four operation distances. Composition of the harvested algal biomass was analyzed. Coral velvet with 5–8 mm length villus was the optimal carrier, since it was durable and with high biomass productivity (6.95–8.11 g m −2 ·day −1 ). Nutrients in the wastewaters were efficiently removed with the COD, TN and TP reduction of over 86.61%, 73.68% and 89.85%, respectively. Wastewater with the low nutrients concentration experienced lower biomass and lipid productivity but larger biodiesel productivity and higher nutrient removal efficiency. In addition, as the operation distance increased, wastewater treatment efficiency was first increased but then decreased, while algal biomass footprint production was decreased. Differences in nutrients removal efficiencies were mainly due to the distance difference, which caused different biofilm culture surface areas and light regimes. The optimal operation distance as a function of the efficient nutrient removal and biodiesel production in this study was 6 cm. Graphical abstract: Highlights: Raceway pond was enhanced by vertical algal biofilm for wastewater treatment. Coral velvet with 5–8 mm length villus was the optimal carrier for attached growth. 7–19 g m −2 ·day −1 of biomass and 122–247 mg m −2 ·day −1 of biodiesel was generated. Over 86.61% of COD, 73.68% of TN and 89.85% of TP were removed. The optimal operation distance between the vertical biofilms was 6 cm.